Revisiting Newmark’s Theory of Translation: To What Extent Is It Appropriate? - Budiman, Asep; Wulandari, Yasinta; Rosyidah, Naeli (Educalitra: English Education, Linguistics, and Literature Journal, 2023)
In the twentieth century, when the study of cultural anthropology suggested that linguistic barriers were insuperable and that language was entirely the product of culture, the translation must be as literal as possible. This resulted in confusion among translators when translating a text, not until they were illuminated by Peter Newmark’s "Approaches to Translation". Newmark's idea has been widely used in translator training courses and combines a wealth of practical examples of linguistic theories of meaning with practical applications for translation. However, in this twenty-first century where translation becomes more complex (e.g. political agenda), Newmark’s theory seems to have a deficiency as it does not pay attention to the role of the translators. Therefore, the translation theory needs to be broadened to take into account the value-driven of the human yardstick framework. The present paper aims to provide a critical evaluation of Newmark's theory of translation and to suggest a new theory. It is concluded that Newmark's theory lacks some important criteria to really reach appropriate translation in some cases. Finally, the “Appropriateness Theory” proposed by Woesler (2021, 2) comes to perfect the previous theories and to meet the demands of this twenty-first century translation.